Reframing Ḥifẓ al-Nasl: Childfree Discourse among Indonesian Celebrities in the Perspective of Maqāṣid al-Usrah - Ahmad Musadad; Alfa Zaidanil Fauzi; Shofiyun Nahidloh; Rudi Hermawan; Muttaqin Choiri (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
The shifting marriage paradigm toward individual autonomy has triggered the childfree trend, challenging Indonesia’s normative-pronatalist values. This study addresses whether childfree constitutes a betrayal of ḥifẓ al-nasl or a contextual realization of maqāṣid when parenting capacity is compromised. The research gap lies in the polarization between sociological and normative studies that fail to integrate socio-legal analysis with family-specific maqāṣid. This qualitative study employs a socio-legal approach, analyzing the narratives of five Indonesian celebrities via virtual loci and a coding framework based on Jamāluddin ‘Aṭiyyah’s Maqāṣid al-Usrah. Findings indicate that childfree among these celebrities is a contextual maqāṣid realization, not a betrayal of ḥifẓ al-nasl. There is a shift from quantitative regeneration (al-tanāsul) to quality of life (al-injāb). This choice serves as a preventive instrument (sadd al-dhari’ah) to avoid parenting injustice and maintain sakīnah amid mental or financial unreadiness. Reframing ḥifẓ al-nasl as a qualitative commitment to human dignity allows contemporary Islamic law to balance individual autonomy with social stability. Consequently, the government should formulate maqāṣid-based family policies prioritizing parenting quality and mental health over fertility targets.